Kedudukan Rumah Tinggal Anak Sebagai Objek Gugatan Harta Bersama dalam Hukum Islam: Perspektif Kepentingan Terbaik - Budi, Kukuh Pramono; Anand, Ghansham; Septiningrum, Shintya Yulfa; Rahmat, Nur Ezan; Nugraha, Xavier (Syariah: Jurnal Hukum dan Pemikiran, 2023)
Children hold a very important role in the development of a country. However, children are generally vulnerable; hence, protecting and ensuring children's rights must be a priority. One example of a condition where children’s rights are put at risk is when a child's residence becomes the object of a joint property lawsuit. In this case, the principle of the best interests of the child needs to be the main consideration in all matters of decision. This study aims to determine the characteristics of the best interests of the child principle in Islamic law and analyze the formulation of the judge's decision regarding the position of the child's residence, which is the object of a joint property lawsuit. This research is normative legal research, using primary and secondary legal materials. The result of this research shows that the principle of the best interests of the child initiated at the Convention on the Rights of the Child has become an important consideration in various laws and regulations in Indonesia, including the Compilation of Islamic Law to the Supreme Court Circular Letter (Surat Edaran Mahkamah Agung, SEMA). As an important principle to be applied in the joint property lawsuit, this study provides three views of the judge's decision formulation, namely: 1) The lawsuit is admissible as there is no explicit norm; 2) It is inadmissible as it is waiting for the child to enter adult age; and 3) It is admissible; however, the distribution is postponed till the child enters adult age. Through this study, the author agreed that the lawsuit is admissible by postponing the distribution until the child reaches adulthood. However, there needs to be some refinement regarding the position of SEMA and the clarity of adult age.